Motif Tukang Becak Mempertahankan Pekerjaanya Ditengah Maraknya Moda Transportasi Aplikasi Di Surabaya - Farista, Zeni (Paradigma, 2022)
Abstract There are several types of conventional transportation in Indonesia, including taxis, buses, public transportation, auto rickshaws, motorbike taxis and also rickshaws. This research discusses conventional modes of transportation, namely pedicabs, which still maintain their jobs amidst the rise of application modes of transportation. The results of this explain, among other things, social conditions which include the pedicab driver’s background and education and economic conditions of the pedicab driver, the pedicab driver’s background which includes personal background, family background, environmental background. The causal motives of the pedicab driver to maintain his job include not being interested in having a side job or switching to being an application transportation driver then there was a failure in his previous job, the objective motive of the pedicab driver to maintain his job is to meet family needs, finance children’s schooling, and pay boarding and establish dream house. This study used qualitative research methods. The focus of this research is to look at the motives of pedicab drivers in maintaining their jobs amidst the rise of application modes of transportation. This research uses the perspective of phenomenological theory initiated by Alfred Schutz. By using this phenomenological approach, it is hoped that it will be able to explain more complexly, in detail and in more depth about the phenomena that are being studied in this study. Keywords: transportation, conventional transportation, application transportation, rickshaws.